Perceptions of Balance Across the Adult Lifespan : A Comparison of Younger and Older Adults - Cross, Anaïs; Ziepke, Alexandra; Hines, Jarrod (My University, 2019)
This project is intended to help explain why older adults may possess a fear of falling from an as-of-yet unexplored angle – one that is purely based on stereotyping and expectations about falls that they may apply to themselves. Although it is generally understood that older adults are more vulnerable to falls than are younger adults, the nature of this belief (or stereotyping) has not yet been investigated. Previous research clarified various risk factors for the development of a fear of falling, including psychological factors such as general anxiety and non-psychological factors such as gender, medication intake, age, and more. However, no one has yet investigated the potential role of stereotyping in the development of a fear of falling. Part one of this study was a questionnaire in which participants answered questions focused on the ability of adults of various ages (i.e., 20-100, by decade) to maintain their balance in general and in specific situations (e.g., getting dressed or undressed). After these lifespan questions, they were asked questions focused on their own balance, how it has changed in the past, and how they expect it to change in the future. Part two of this study was a questionnaire in which participants answered a revised version of part one, as well as questions about their personal experiences with falling. If participants had experienced a significant fall in their life, then they were asked circumstantial questions regarding that fall. All participants were then asked about their potential fear of falling and about if they know someone else who has fallen in the past ten years. If participants knew someone else who had experienced a fall, then they were asked circumstantial questions regarding that fall. For study one, we hypothesized that younger adults would rate older adults as having worse balance in general and in specific situations than older adults would. We also hypothesized that both younger and older adults would rate balance worse for each age group as age increased. For study two, we hypothesized that having experienced a fall or knowing someone who had experienced a fall would be associated with a greater fear of falling, especially for older adults.
Color poster with text, charts, and graphs.
Keywords: Older adults; Fear; Falls; Posters; Department of Psychology